Regional mapping of groundwater resources in data-scarce regions: the case of Laos - Viossanges, Mathieu; Pavelic, Paul; Rebelo, Lisa-Maria; Lacombe, Guillaume; Sotoukee, Touleelor (MDPI, 2018)
This study focuses on Laos, a landlocked nation located in South-East Asia with sub-tropical climate and highly seasonal rainfall distribution. Laos is one of the world’s least developed countries, and currently witnesses an unprecedented level of development that is highly reliant on its natural resources, including groundwater. There is currently very limited data and no nationwide assessment of shallow (<30 m) groundwater resources to support sustainable management. This study provides a first step towards addressing this issue by (i) identifying the major aquifer units of the country; (ii) integrating localized data and regional maps into an assessment of the groundwater potential; and (iii) producing quantitative maps of key hydrogeological indicators. Eight aquifer units have been described and evaluated: (i) Basement aquifers, (ii) Volcanic aquifers, (iii) Schists, (iv) Paleozoic sedimentary, (v) Karsts, (vi) Limestones, (vii) Mesozoic sedimentary and (viii) Alluvial sediments. The Mesozoic sandstones and the Alluvial aquifers are the most extensive and productive hydrogeological systems in the country. The Volcanic and Karstic aquifers, although poorly known, might also have important potential. This assessment, along with the maps of quantitative aquifer indicators, provide a significant improvement in both spatial resolution and accuracy compared to previously available information. It will likely support improved management plans and the identification of areas with higher potential for groundwater development.